Clinical Evaluation of Verapamil in Angina Pectoris - Sandler, G. (1968)
A controlled double-blind study of verapamil in 16 anginal patients used two dose levels—40 mg. t.d.s. and 120 mg. t.d.s.—and was compared with propranolol 100 mg. t.d.s. At the higher dosage verapamil produced a significant improvement in frequency of angina, trinitrin consumption, and exercise tolerance, and had a favourable and significant effect on the amount and duration of ischaemic S–T depression occurring in the electrocardiogram during exercise. In the lower dose verapamil produced significant subjective improvement but no objective benefit in the electrocardiogram. No significant differences were found between the favourable results with the higher dosage of verapamil and propranolol. The action of verapamil is not fully understood, but its favourable effects in angina may be due to a direct action on the myocardium, possibly with accompanying coronary vasodilatation.